Pembelajaran Gelombang Bunyi Menggunakan Alat Musik Suling dan Gawai pada Pelajaran IPA SMP di Masa Pandemi Covid-19 - Syakti Perdana Sriyansyah; Khairil Anwar (Journal of Natural Science and Integration, 2021)
ABSTRACTThe COVID-19 pandemic requires teachers to think carefully and creatively in designing learning so that it remains interactive and appropriate to achieve the learning goals. Physics learning with using a flute and a smartphone described in this paper is the result of a thought process about how students can still conduct experiments from home using simple equipment to measure the speed of sound in the air and at the same time learn the concepts of loudness and pitch of sound. A total of 37 eighth grade students in 2020/2021 academic year and 23 students in 2018/2019 acadeymic year at a private junior high school in Bekasi were involved in a pre-experimental study with a one-group posttest only design. A set of 10-item multiple-choice diagnostic tests taken from the Mechanical Wave Conceptual Survey and summative tests in the form of structured questions were arranged to test students' conceptual understanding after receiving sound wave learning. The average of diagnostic test and summative test in the 2018/2019 and 2020/2021 academic years were 30, 48 and 60 respectively out of 100 with a summative test completion percentage of 35% in 2018/2019 and 70% in 2020/2021 . Keywords: physics experiment, sound waves, recorder, smartphoneABSTRAK Masa pandemi Covid-19 menuntut guru untuk terus berpikir secara hati-hati dan kreatif dalam merancang pembelajaran agar tetap interaktif dan tepat mencapai tujuan pembelajaran yang ditetapkan. Pembelajaran dengan menggunakan suling dan berbantuan gawai yang dipaparkan dalam tulisan ini merupakan hasil dari proses berpikir tentang bagaimana siswa tetap dapat melakukan eksperimen dari rumah memanfaatkan peralatan sederhana untuk mengukur kelajuan gelombang bunyi di udara dan sekaligus mempelajari konsep kekerasan bunyi (loudness) dan tinggi nada (pitch) bunyi. Siswa kelas delapan sebanyak 37 siswa tahun ajaran 2020/2021 dan 23 siswa tahun ajaran 2018/2019 pada salah satu sekolah menengah pertama swasta di Kota Bekasi dilibatkan dalam penelitian pre-experiment dengan desain one-group posttest only. Seperangkat tes diagnostik berbentuk pilihan ganda sebanyak 10 butir yang diambil dari Mechanical Wave Conceptual Survey dan tes sumatif berbentuk uraian disusun untuk menguji pemahaman konsep siswa setelah mendapatkan pembelajaran gelombang bunyi. Rata-rata tes diagnostik dan tes sumatif pada tahun ajaran 2018/2019 dan 2020/2021 berturut-turut sebesar 30, 48 dan 60 dari maksimum nilai 100 dengan persentase ketuntasan tes sumatif sebesar 35% di 2018/2019 dan 70% di 2020/2021.Kata kunci: eksperimen fisika, gelombang bunyi, suling, gawai